SPEECH ACTS IN THE NOVEL “SPEAK” BY LAURIE HALSE ANDERSON - Mustika Transmawati (Universitas PGRI Palembang, 2020)
The research objectives are to find out:(1) what speech acts are found in the novel “Speak” by Laurie Halse Anderson, (2) the forms used to express speech acts meaning in this novel, (3) what the kinds of speech acts appear dominantly in this novel, (4) the ways of the novelist moral values are expressed in speech acts of this novel, and (5) the theoretical implication for English Language Teaching. Qualitative methods and content analysis were used in this research. Documentation, book reviewer, and interview were used as data collection. Triangulation was used to get validity. Research results are (1) all speech acts types appeared,(2) The were 4 directives forms, 4 commisive forms, 6 representatives forms, 3 declarations forms, 12 expressive forms,(3) Expressive was dominant,(4) The novelist expressed moral values through expressive dominantly. (5) The novel